PROX1: A Lineage Tracer for Cortical Interneurons Originating in the Lateral/Caudal Ganglionic Eminence and Preoptic Area - Rubin, Anna Noren (Public Library of Science, 2013)
The homeobox-encoding gene Prox1 and its Drosophila homologue prospero are key regulators of cell fate-specification. In the developing rodent cortex a sparse population of cells thought to correspond to late-generated cortical pyramidal neuron precursors expresses PROX1. Using a series of transgenic mice that mark cell lineages in the subcortical telencephalon and, more specifically, different populations of cortical interneurons, we demonstrate that neurons expressing PROX1 do not represent pyramidal neurons or their precursors but are instead subsets of cortical interneurons. These correspond to interneurons originating in the lateral/caudal ganglionic eminence (LGE/CGE) and a small number of preoptic area (POA)-derived neurons. Expression within the cortex can be detected from late embryonic stages onwards when cortical interneurons are still migrating. There is persistent expression in postmitotic cells in the mature brain mainly in the outer cortical layers. PROX1(+ve) interneurons express neurochemical markers such as calretinin, neuropeptide Y, reelin and vasoactive intestinal peptide, all of which are enriched in LGE/CGE- and some POA-derived cells. Unlike in the cortex, in the striatum PROX1 marks nearly all interneurons regardless of their origin. Weak expression of PROX1 can also be detected in oligodendrocyte lineage cells throughout the forebrain. Our data show that PROX1 can be used as a genetic lineage tracer of nearly all LGE/CGE- and subsets POA-derived cortical interneurons at all developmental and postnatal stages in vivo.